Kajian terhadap projek perumahan di Kelantan - Che Ibrahim, Nor Adilah (2005)
The housing projects in Kelantan are not only constructed by the government but also by the private sectors. In Kelantan, the private sectors are facing problems whereby they are unable to sell the houses to the non bumiputeras. This is due to the government policy that the land title and houses is only for the people in Kelantan. The objectives of this study are to identify the process of State Land application in Kelantan, to identify the approval process in selling housing units to non bumiputeras, to identify the factors contributing to the failure in selling housing units to bumiputeras in Kelantan and lastly to identify the preferable housing price range affordable among the bumiputeras in Kelantan. The scope of this study is focused on housing projects in Kelantan. The literature review consists of housing in Malaysia, the parties that are involved in housing industry, the laws which are related to the housing industry, feasibility study, the importance of feasibility study, scope and approaches in feasibility study, housing loan and problems of surplus in housing industry. The methodologies that have being used are literature review, pilot study and data analysis. The mean index method using SPSS is also being used to analyze the data. From the study, the approval process in selling housing units to non-bumiputeras takes about 6 to 12 months to be processed. The housing price rang affordable is between RM 46,000 to RM 90,000.